Valuation and Recording the Value of Innovation Objects in the Accounting System - OVSIUK, N. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The problems of valuating and recording the value of innovation objects in the system of accounting and reporting are investigated. It is argued that one of the factors hindering the development of innovation is insufficient information support covering a set of primary and consolidated data, the organization of storage of accumulated information and methods of its presentation and transformation. The main valuation models used by business entities to include the value of innovation objects in the economic transactions are identified. It is established that the commercial use of innovation objects requires calculation of market or other value. The main methodological approaches to valuation of innovation objects and their impact on the formation of the value of innovation objects are proposed, taking into account these objects’ characteristics, specifics of the economic activities in which they are exploited, and availability of information on a group of objects, which determines the choice of appropriate valuation approach. The ways of valuating innovation objects at company level are highlighted. Methodological approaches to recording business transactions with innovation objects in the accounting and reporting system are elaborated, which will contribute in the sound assessment of innovation objects and their correct recording in the accounting system of a business entity and ensure effective management of innovation.